Klucz kodowania - Pieniężny, Dawid
The research task consists of conducting a field study and a research trip to conduct this pilot study in terms of the suitability of the research tool for the creation of a doctoral dissertation. The author intends to print 120 questionnaires (including 20 reserve ones), and then verify their usefulness on an identical research sample, in one place in the country - the Diocese of Szczecin and Kamień, which is one of the most secularized dioceses in Poland, according to the reports of the Institute of Statistics of the Catholic Church. The research task therefore includes a trip and field research aimed at assessing the prepared research tool and, consequently, improving it, in order to create the final version of the tool.
Keywords: pilot study; research tool; survey questionnaire